Sarcopenia in Urothelial Bladder Carcinoma: A Narrative Review - Constantin Radu Vrabie; Andreea Ioana Parosanu; Cornelia Nitipir (Medicina)
Background and Objectives: Urothelial bladder carcinoma includes a spectrum of malignant lesions with heterogeneous molecular, biological, and clinical features and a variable risk of progression from non-muscle-invasive bladder cancer (NMIBC) to muscle-invasive disease (MIBC) and ultimately to metastatic urothelial carcinoma (mUC). Sarcopenia, a condition secondary to a catabolic state, is characterized by progressive loss of skeletal muscle mass and function and is highly prevalent across all stages of bladder cancer. This review aims to synthesize current evidence regarding the clinical impact of sarcopenia and its dynamic changes throughout the disease course. Materials and Methods: A narrative literature review was conducted using PubMed, Scopus, and Cochrane databases, incorporating the most relevant published sources. Search terms included “bladder carcinoma”, “sarcopenia”, “body composition”, “NMIBC”, and “MIBC”. Case reports and congress abstracts were excluded. Results: In NMIBC treated with intravesical Bacillus Calmette–Guérin (BCG), sarcopenia has been shown to have a negative predictive value in some studies. Among patients receiving neoadjuvant chemotherapy (NAC) for MIBC, sarcopenia has been associated with increased toxicity, dose reductions, and treatment delays. In the context of radical surgery, sarcopenia correlates with increased postoperative mortality and a higher rate of severe complications. In mUC, low muscle mass is a negative prognostic factor regardless of treatment type and is associated with chemotherapy-related hematologic toxicity, although it does not appear to predict immune-related adverse events (irAEs). Conclusions: Sarcopenia is a highly prevalent and clinically relevant phenotype of urothelial bladder cancer patients, impacting prognosis, treatment response, and chemotherapy toxicity. Incorporating sarcopenia with other relevant components of body composition (BC) and systemic inflammatory markers may facilitate the development of more robust risk scores. Current evidence is primarily limited by the retrospective design of most studies. Future prospective research is needed to clarify the prognostic role of sarcopenia and support its integration into routine clinical decision-making.